Smile Preferences of Orthodontists and Patients from Frontal View about Gingival Display, Occlusal Cant and Smile ARC: A Study from Isra Dental College - Mooli, Sadia Asif Samdani, Sadaf Siddiqui, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Was to determine preferences of orthodontists and patients about gingival display, occlusal cant and smile arc. Material and methods: This descriptive cross sectional study was conducted on 65 participants (15 orthodontists and 50 patients). The inclusion criteria were participants who gave consent, Pakistani nationals, age from 20 to 45 years, and Layperson/patients. Exclusion criteria were mentally retarded, uncooperative, color blinded individual and dental students, dental attendants and technicians. Adobe photoshop CS6 was used to alter the smile arc, occlusal plane and gingival display incrementally. Student t test was run to compare the smile preferences between orthodontists and patients. P≤0.05 was considered significant. Results: The mean age of the participants was 33.15±6.29 years. Females (n=38, 58.5%) were more than males (n=27, 41.5%). For 0mm gingival show the score assigned by laypersons (6.86±0. 756) was statistically higher than orthodontists (6.40±0.507) (P=.031). Gingival show of 5mm was less acceptable to laypersons (1.92±0.752) than orthodontists (3.27±0.594) statistically (P<0.001). Ideal smile arc was attractive for both laypersons (8.04±0.638) and orthodontists (9.33±0.724) but statistically more among orthodontists (P<0.001). Significant difference was found between perception of orthodontists and laypersons for normal smile (P=.034) and canted smile (P<0.001). Conclusion: Significant differences exist between opinions of orthodontists and laypersons in evaluating gingival display, smile arc and occlusal cant. Patient should be participated in treatment planning involving alteration of these smile parameters. Keywords: Smile perception, gingival show, smile arc, occlusal cant